ANALISIS RASIO KEUANGAN PENDEKATAN CAPITAL ADEQUACY RATIO (CAR) DALAM RANGKA MENILAI TINGKAT KESEHATAN BANK (Studi Kasus PT. BPR Depo Mitra Mandiri, Depok) - Sri Setiawati (POLITEKNIK LP3I JAKARTA, 2020)
This research was written by Sri Sriawati and Meulya Daughter, In May 2015 until September 2015, with the title: Analisys of Financial Ratio By CAR Model to Asses Bank Performance. (Case Study PT. Bank Rural Depo Mitra Mandiri, Depok). The aim of this study was to obtain information on whether the calculation of financial ratios with CAR (Capital Adequacy Ratio) can be used to assess the soundness of the bank and find out how strong the calculation of financial ratios with CAR (Capital Adequacy Ratio) to assess the level of health. This study uses descriptive analysis, which is explained by using the bank's soundness by calculating CAR (Capital Adequacy Ratio). Techniques of data collection is done by studying various books literature and field research such as direct observation, interviews, and collection of data concerning documents to be examined, whereas the data analysis technique used is quantitative analysis, namely by calculating and lays out the data that has been obtained by reference PBI 8/18 / PBI / 2006 dated October 5, 2006. From the results of the study showed that the CAR (Capital Adequacy Ratio). can be used in assessing the health of banks. Results of the analysis of bank health using the calculation of CAR (Capital Adequacy Ratio), as follows In the period from December 31, 2011 amounted to 46.50%,In the period from December 31, 2012 amounted to 43.44%, In the period from December 31, 2013 amounted to 37.98%,In the period December 31, 2014 amounted to 42.37%. CAR PT. BPR Depo Mitra Mandiri above is healthy has been above the Bank Indonesia regulations PBI 8/18 / PBI / 2006 dated October 5, 2006 at 8%.Key words: Financial ratio, Bank healthy, Capital Adequacy Ratio